2017
DOI: 10.1134/s1075700717010038
|View full text |Cite
|
Sign up to set email alerts
|

School graduates from small towns in Russia: Educational and migration strategies

Abstract: ⎯This paper used the results of a research project that was implemented at the Institute for Social Analysis and Forecasting of the Russian Academy of National Economy and State Service under the President of the Russian Federation in 2015. The data of the quantitative survey of school graduates from the 11th grade of secondary schools in small Russian towns, as well as the materials of expert interviews with representatives of the municipal education departments and school management. The main conclusion of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…section). This result is rather expected, since the previous qualitative studies showed a clear desire of the youth to flee the periphery for good both at upperschool and student ages (Florinskaya 2017;Florinskaya and Roshchina 2006).…”
Section: Introductionsupporting
confidence: 62%
“…section). This result is rather expected, since the previous qualitative studies showed a clear desire of the youth to flee the periphery for good both at upperschool and student ages (Florinskaya 2017;Florinskaya and Roshchina 2006).…”
Section: Introductionsupporting
confidence: 62%
“…Migration for educational purposes has become quite widespread among young people from small cities (Niedomysl ; Florinskaya ; Mkrtchyan ), as it has become an established part of the process of transitioning to adulthood (Jones ). These young people are not real ‘emigrants’ as they have not yet made the decision to permanently migrate.…”
mentioning
confidence: 99%
“…[10], Zakharenko R. [11], Florinskaya Yu.F. [12], Zborovsky G.E., Ambarova P.A. [13], Raghuram P. [14] are devoted to study of interconnections between the processes of education and the migration component.…”
Section: Methods Of Investigation and Literature Reviewmentioning
confidence: 99%